Treatment with glial derived neurotropic factor (GDNF) attenuates oxidative damages of spinal - Tao Li; Qi Li; Hui Gong; Zhuo-fu Chen; Xia-wu Peng (Elsevier, 2016)
Spinal cord injury (SCI) is a serious and debilitating issue being suffered by wide population worldwide. Extensive treatment approaches have been tested and being verified for their efficacy. Owing to the nature of central nervous system (CNS), the resident stem cells would be triggered in response to any sort of trauma with nerve factors as their communication signals. Apart from physical injuries, damages due to oxidative stress also need to be addressed while CNS repair mechanism takes place. This study looks at the potential of glial derived nerve factor (GDNF) in addressing the SCI in regard to oxidative damages. A total of 60 Wistar rats were clustered into five groups and GDNF at various concentrations was tested in each group. Assessments in terms of oxidative stress parameters were noted and analyzed accordingly. It was noted that GDNF had reduced oxidative damages and increased the levels of anti-oxidants in dose-dependent manner (p < 0.05). Though treatment with 10 mg/mL and 20 mg/mL showed significant changes as compared to control group, these treatment modalities remained insignificant among each other. In conclusion, we demonstrated that GDNF exerted a neuro-protective effect on CNS by inducing anti-oxidants and reducing the levels of oxidative stress in SCI induced rat models.